KEPERCAYAAN DIRI DITINJAU DARI BODY IMAGE PADA SISWI KELAS X SMA - Wati, Ida; Wati, Ida; sarinah, Sarinah; Hartini, Sri; Hartini, Sri (Jurnal Ilmiah Psyche, 2019)
Abstract : This study aims to determine the relationship between body image and self-confidence. The hypothesis proposed in this study is that there is a positive correlation between body image and self-confidence with the assumption that the higher is body image,  the higher will self-confidence be, and conversely the lower is body image, lower will self-confidence be. This research subjects were grade ten female students in a private school in Medan consisting of 125 students who were selected using purposive sampling technique. Data were obtained from a scale for measuring body image and self confidence. The calculation was performed through the prerequisite test analysis (assumption) that consisted of a test for normality and linearity. Data analysis used was Product Moment through SPSS 21 for Windows. The results of data analysis showed that  r = 0,365, and p = 0.000 (p <0.05), indicating that there is a positive relationship between body image and self-confidence. The results of this study indicated that the contribution (R2) given variable of body image on self-confidence was 13.3 %, while the remaining 87.7 % was  influenced by other factors not examined. From these results it is concluded that the hypothesis can be accepted.   Key word: Body Image, Self-Confidence, Ten Grade Female Students   Abstrak : Penelitian ini bertujuan untuk mengetahui hubungan antara body image dan kepercayaan diri. Hipotesis yang diajukan pada penelitian ini adalah ?ada hubungan positif antara body image dan kepercayaan diri? dengan asumsi bahwa semakin tinggi body image maka semakin tinggi kepercayaan diri dan sebaliknya semakin rendah body image maka semakin rendah kepercayaan diri. Subjek penelitian yang digunakan dalam penelitian ini adalah siswi kelas X di salah satu SMA di kota Medan sebanyak 125 orang yang dipilih dengan menggunakan purposive sampling. Data diperoleh dari skala untuk mengukur body image dan kepercayaan diri. Perhitungan dilakukan melalui uji prasyarat analisis (uji asumsi) yang terdiri dari uji normalitas dan uji linearitas. Analisis data dengan menggunakan Analisa Product Moment melalui bantuan SPSS 21 for Windows. Hasil analisis data menunjukkan r =0,365, dan p = 0.000 (p < 0.05) yang menunjukkan bahwa ada hubungan positif ada body image dan kepercayaan diri. Hasil penelitian ini menunjukkan bahwa sumbangan (R2) yang diberikan variabel body image terhadap kepercayaan diri adalah sebesar 13,3 persen, selebihnya 87,7  persen dipengaruhi oleh faktor lain yang tidak diteliti. Dari hasil penelitian ini dapat ditarik kesimpulan bahwa hipotesis yang diajukan dapat diterima.   Kata Kunci: Body Image, Kepercayaan Diri, Siswi Kelas X SMA